2013
DOI: 10.3892/mmr.2013.1376
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hTERT in potentially malignant colorectal laterally spreading tumors

Abstract: Abstract. Human telomerase reverse transcriptase (hTERT) is the main subunit of the core enzyme telomerase, which consists of three subunits. Telomeres are essential for chromosomal stability and integrity, protecting the ends of chromosomes from degradation and preventing chromosomal end fusions and recombination. A loss of telomere function is a major mechanism for the generation of chromosomal abnormalities. Telomere shortening leads to mutations, chromosome rearrangements and translocations. Colorectal lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Our results are in agreement with the previous studies which concluded that hTERT protein has an iportant role in advanced malignancy on some cancer types including breast cancer, gastric cancer, colorectal cancer, meningiomas, and spinal chordoma [35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with the previous studies which concluded that hTERT protein has an iportant role in advanced malignancy on some cancer types including breast cancer, gastric cancer, colorectal cancer, meningiomas, and spinal chordoma [35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…The hTERT immunostaining score was calculated with a semi-quantitative scoring system as the intensity (0, no staining; 1, weak staining; 2, moderate staining; 3, strong staining) and the percentage (extent staining) of tumor cells that were stained (0, <10% of tumor cells stained; 1, 10–50% of positive cells; 2, >50 and <75% of positive cells; 3, >75% of positive cells). An overall score was obtained as the product of the intensity and distribution of positive staining ( 19 ). Cases with 0 points were considered to be negative (0), cases with a final score of 1–3 as weakly positive (1+), cases with a final score of 4–7 as moderately positive (2+) and cases with a final score of >7 as strongly positive (3+).…”
Section: Methodsmentioning
confidence: 99%
“…The technique was also performed on brain cryo-sections and non-malignant brain tissue sections along with lung, kidney and thyroid tissue sections and their results were compared for reproducibility. Expression of protein human Telomerase Reverse Transcriptase (hTERT), implicated as a proliferation marker in various cancers (12)(13)(14), was used to verify and replicate the procedure, and quantitatively analyze and statistically validate the methodology using fluorescence tagged antibody. Subsequently, expression of other nuclear and cytoplasmic fluorescein isothiocyanate (FITC) tagged protein targets, namely High Mobility Groupa1 (HMGa1), Kinesin Family Member14 (KIF- 14) and Synaptophysin, was also checked on glioma tissues.…”
mentioning
confidence: 99%